Antagonistic Test of Aspergillus niger and Trichoderma harzianum Against the Toxigenic Aspergillus flavus - Catur Putri Enggit Reksiana; Wiwin Windriyanti; Nijma Nurfadila; Ramadhani Mahendra Kusuma (Future Science, 2023)
Aspergillus flavus is a post-harvest fungus that often contaminates foods and feeds, causing damage to commodities, and causing health problems for humans and animals. This study aims to determine the effectiveness of the fungi Aspergillus niger and Trichoderma harzianum as antagonist fungi against A. flavus in vitro using the direct opposition method. The fungus A. flavus and the antagonist fungus were isolated in the same petri dish. The results showed the highest percentage inhibition of growth after seven days of incubation was shown by A. niger 5, was 95.83%, while the percentage inhibition of growth by T. harzianum 4, was 71.43%. A. niger had a higher percentage inhibition of growth than T. harzianum which ranged from 90 – 96%, while the lowest percentage inhibition of growth of T. harzianum ranged from 71 – 90%. Both of these fungi are recommended as an effective and safe alternative for controlling the toxigenic A. flavus because they have an inhibition percentage of more than 60%. Inhibition mechanism of antagonist fungi through competition of growth space and limited nutrients.